2010
DOI: 10.1159/000319842
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Viruses, Eosinophilia and Their Roles in Childhood Asthma

Abstract: With the advent of highly sensitive and specific screening of respiratory specimens for viruses, new viruses are discovered, adding to the growing list of those associated with wheezing illness and asthma exacerbations. It is not known whether early childhood infections with these viruses cause asthma, and, if so, what exactly are the pathophysiologic mechanisms behind its development. The current consensus is that respiratory viral infection works together with allergy to produce the immune and physiologic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 197 publications
0
9
0
Order By: Relevance
“…Most importantly, the presence of eosinophils cells was a parameter measured during the characterization of wheezing in patients infected with hMPV [ 186 ]. Since the hMPV infection leads to the recruitment of eosinophils to the lung, and these cells are associated with the development of wheezing and asthma, it is possible to suggest that eosinophils are the reason why these symptoms are present during a hMPV infection [ 215 ].…”
Section: Differential Regulation Of the Innate Immune Response By mentioning
confidence: 99%
“…Most importantly, the presence of eosinophils cells was a parameter measured during the characterization of wheezing in patients infected with hMPV [ 186 ]. Since the hMPV infection leads to the recruitment of eosinophils to the lung, and these cells are associated with the development of wheezing and asthma, it is possible to suggest that eosinophils are the reason why these symptoms are present during a hMPV infection [ 215 ].…”
Section: Differential Regulation Of the Innate Immune Response By mentioning
confidence: 99%
“…The complex interaction between viral infections and the development of asthma is detailed in several review articles [28,29]. These studies highlight both inconsistencies in the literature and the nuanced…”
Section: Early Life Infections and The Development Of Asthmamentioning
confidence: 99%
“…Repeated or chronic respiratory infections can damage respiratory epithelial integrity (by impairing its defensive function) and lead to eosinophil accumulation and sustained release of cysteinyl leukotrienes and other inflammatory mediators. This causes chronic inflammation and persistent respiratory airway hyperresponsiveness, promotes airway remodeling and dysfunction, enhances susceptibility to pathogens and common allergens, and promotes a continued decline in lung function in children with recurrent wheezing [6,7]. A study of asthma patients with less well-controlled asthma showed a close relationship between airway microbial infections and airway hyperresponsiveness [8].…”
Section: Introductionmentioning
confidence: 99%